La paix américaine pour les Balkans - Lukic, Reneo; Lynch, Allen (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1996)
Yugoslavia's loss of strategic value since the end of the cold war has determined the scope of us engagement in the War s of Yugoslav Succession. In June 1991, therefore, the us allowed the EC and the UN to preserve Yugoslav unity and then contain the effects of the several wars launched by Serbia in the region. Bill Clinton, after rejecting George Bush's policy of "Realpolitik" during the 1992 election campaign in favor of defending the victims of aggression, quickly confirmed the essential continuity of us policy in the Balkans. Throughout the Clinton Presidency, the us has sought to contain the effects of the Yugoslav wars rather than reverse the consequences of aggression, and has relatedly sought to exclude the possibility of a significant combat role for us ground forces. Rhetoric aside, us policy has sought to encourage a settlement that reflects the military facts on the ground. The Dayton accords of November 1995 reflect these considerations in detail. Whatever the long-term effects of the Dayton "peace", one consequence is certain : the marginalization of Western Europe as a foreign policy actor within Europe itself